2022
DOI: 10.3390/plants11060803
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Chloroplast Activity with Plant Growth: Clues Point to TOR

Abstract: Photosynthesis is the defining function of most autotrophic organisms. In the plantae kingdom, chloroplasts host this function and ensure growth. However, these organelles are very sensitive to stressful conditions and the photosynthetic process can cause photooxidative damage if not perfectly regulated. In addition, their function is energivorous in terms of both chemical energy and nutrients. To coordinate chloroplast activity with the cell’s need, continuous signaling is required: from chloroplasts to cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…Nutrient limitation or environmental stress lead to the inactivation of TOR, which slows growth and promotes nutrient recycling. TOR also influences photosynthesis in plants and algae, a phenomenon that up to now was only explained by transcriptional regulation of nuclear-encoded chloroplast genes (Dong et al, 2015;Sun et al, 2016;Imamura et al, 2018;Upadhyaya and Rao, 2019;D'Alessandro, 2022). Here we set out to determine whether TOR is involved in the post-transcriptional regulation of photosynthesis.…”
Section: Main Textmentioning
confidence: 99%
“…Nutrient limitation or environmental stress lead to the inactivation of TOR, which slows growth and promotes nutrient recycling. TOR also influences photosynthesis in plants and algae, a phenomenon that up to now was only explained by transcriptional regulation of nuclear-encoded chloroplast genes (Dong et al, 2015;Sun et al, 2016;Imamura et al, 2018;Upadhyaya and Rao, 2019;D'Alessandro, 2022). Here we set out to determine whether TOR is involved in the post-transcriptional regulation of photosynthesis.…”
Section: Main Textmentioning
confidence: 99%
“…Nutrient limitation or environmental stress leads to the inactivation of TOR, which slows growth and promotes nutrient recycling. TOR also influences photosynthesis in plants and algae, a phenomenon that up to now was principally explained by transcriptional regulation of nuclear-encoded chloroplast genes ( 7 11 ). The possible posttranslational regulation of photosynthesis by TOR was recently proposed ( 12 ), although it is unclear whether it is direct, and a specific mechanism has yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…TOR signalling plays a crucial role in the development and function of chloroplasts (Song et al, 2021; Li & Kim, 2022; Zhang et al, 2022). By modulating the synthesis and degradation of chloroplast proteins, TOR can influence the morphology, quantity, and functionality of chloroplasts (Riegler et al, 2021; D'Alessandro, 2022). Further research has indicated that inhibition of the TOR signalling pathway impairs function and accelerates leaf senescence (Quilichini et al, 2019; D'Alessandro, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…By modulating the synthesis and degradation of chloroplast proteins, TOR can influence the morphology, quantity, and functionality of chloroplasts (Riegler et al, 2021; D'Alessandro, 2022). Further research has indicated that inhibition of the TOR signalling pathway impairs function and accelerates leaf senescence (Quilichini et al, 2019; D'Alessandro, 2022). However, the understanding of how TOR affects cucumber leaf senescence and whether TOR regulates leaf ageing through the modulation of ROS‐induced chloroplast damage in cucumber leaves remains limited.…”
Section: Introductionmentioning
confidence: 99%